Англи, монгол хэлэнд тэмдэг нэрийн утгыг бууруулах үзэгдэл илрэх нь: The Expression of Diminutive of Meaning of Adjectives in English and Mongolia - Ts., Munkhdelger (Mongolian Journal of Foreign Languages and Cultures, 2023)
Adjective (eng - adjective, russ - имя прилагательельное) is an English and Mongolian word that indicates a characteristic of a phenomenon or situation and is a component of the vocabulary. The main purpose of this short article is to study how to express and form the diminutive of meaning of adjectives in English, Mongolian. To observe and describe phenomena related to the diminutive of the meaning based on the literature in the two languages.